Do international students and temporary foreign workers pay more than Canadian-born individuals in the rental market? - Wendy Kei; Feng Hou; Haozhen (Economic and Social Reports)
Amid growing concerns in Canada over housing affordability, questions have arisen about non-permanent residents’ experience in the Canadian rental market. This study uses data from the 2021 Census of Population to examine whether international students and temporary foreign workers face higher rental costs than the Canadian-born population (non-immigrants) and longer-term immigrants (those who were admitted more than five years preceding the census year). It also explores the factors contributing to disparities in rental expenses among these groups.